Beyond Words: Tapping the Potential of Digital Diaries While Exploring Young Adults’ Experiences on Apps - Rita Alcaire; Ana Marta M. Flores; Eduardo Antunes (Societies, 2024)
In the dynamic landscape of online interactions, this article explores the use of digital diaries to unravel the intricacy of Portugal young adults’ experiences within the realm of apps and their connection to gender dynamics. By designing a digital participatory research method, we were able to reflect on the participants’ experiences in maintaining the requested diaries, scrutinize the major themes in the narratives generated through this approach, and examine how participants interacted with the prompts sent to them. Therefore, we delved into how participants both challenged and (re)negotiated these solicitations and how their agency led to an untapped reservoir of insights for the project in ways that went beyond words. There were visual and non-verbal elements that brought insights into young adults’ interactions with mobile applications, offering a comprehensive exploration of four key themes: mobile apps as part of young adults’ routines, between performance and authenticity, making the diaries their own, and elaborating on feelings. We also explored diary methods at the convergence of various disciplines and their high potential for contributing to topics related to gender, mental health, productivity, relationships, online identity management, apps in everyday life, intimacy, and more in creative ways.